Teaching Neuroscience as a Liberal Art - Giraldez, Fernando (Frontiers in Education, 2020)
This article describes a two-decade experience in teaching “Neurosciences for the Humanities: art, philosophy and the brain”. The course is a discussion about sensory physiology, knowledge and the arts. The physiology of the senses provides interesting insights into how we get knowledge of the world and its reliability. This is a major topic in the philosophical tradition, which in turn leads to other interesting and timely questions such as what is science, belief, pseudoscience or post-truth. With respect to the arts, the course focuses on painting and music to discuss the perception of art, the neuroscience behind artistic innovations, les règles d’art and the idea of artists as intuitive neuroscientists. The course ends with a general discussion on “genes and culture”, using the study of “critical periods” and brain plasticity to illustrate the complex interplay between “nature and nurture”. The aim is at bringing a biological perspective to some classical “problems of the mind”, but with full respect towards the philosophical tradition. It is an opportunity to look at the work of great scientists, philosophers, painters and musicians with another eyes, and to learn and enjoy the contributions of those giants. An account of materials used in lectures, discussions and demos, as well as some examples of the teaching strategies are provided.